Wound Healing Activities of Hydrolyzed Virgin Coconut Oil (HVCO) and Fucoidan Combination: An In Vitro Assay - Sagala, Evayanti Meiliana; Silalahi, Jansen (Asian Journal of Pharmaceutical Research and Development, 2019)
combination, in the NIH 3T3 cell line using in vitro assay, and compared with single HVCO and single fucoidan. Methods: NIH 3T3 Cell viability and proliferation were assessed using the MTT method, migration activity was assessed using scratch wound healing assays and expression of COX-2 and VEGF protein were determined using immunocytochemistry (ICC). Results: The results from the proliferative activity assay show that the effective concentrations for all samples were 31.25 μg /ml. NIH 3T3 cells migration activity assay showed that the best combination of the HVCO and fucoidan was 50:50. From COX 2 and VEGF protein expression test results, the combination of HVCO and fucoidan has a higher percentage of expression than single HVCO or single fucoidan Conclusion: The results reveal that the combination of HVCO and fucoidan has better wound healing activity than single HVCO or single fucoidan